GE_GERICHTE P/18684/2023 vom 29. Juli 2024 - GE Cour de justice (2024)
PLAINTE PÉNALE;LÉSÉ;APPRÉCIATION DES PREUVES;VOL(DROIT PÉNAL);DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);VIOLATION DE DOMICILE;TENTATIVE(DROIT PÉNAL);RÈGLEMENT (UE) 2018/1861;EXPULSION(DROIT PÉNAL) | CP.139; CP.22; CP.144; CP.186; LEI.115.al1.leta; CP.30